Urban Floating Farming Implementation: Introduction of Techniques and Modification as an Alternative to Farmers in the Acid Peatlands of the Suburbs - Dienny Redha Rahmani; Gabriel Tonga Noweg; Hanny Maria Caesarina; Wahyunah Wahyunah; Kintan Permata Sari (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2020)
Peatlands - as a wetland area with distinctive characteristics - have its own challenges and difficulties for farmers to grow rice, especially in the Anjir Pasar Seberang area which is one of a suburban area of South Kalimantan, Indonesia. The planting and harvest period can only be done once a year when the land experiences a receding period during the dry season. Thus, farmers need other income alternatives to fill the vacancy during the high season. Floating farming which is the local wisdom of the people in several countries in Southeast Asia is one alternative that can be used when the high tide arrives. Several studies on the modification of this method on a household and urban scale have been carried out. Therefore, it can be one of the solutions for the farming community. The introduction of the modified Farming Methods and Techniques was carried out to provide farmers with other income options besides conventional farming. The local community is interested in this method because of its ease of handling